The effects of mind-body exercise on anxiety and depression in older adults: a systematic review and network meta-analysis - Dong, Yangjian; Zhang, Xinxin; Zhao, Rongting; Cao, Lan; Kuang, Xiaoqin; Yao, Jiwei (Frontiers in Psychiatry, 2024)
i. Background: Limited research directly compares the clinical effects of different types of mindbody exercises on anxiety and depression in older adults. Therefore, we conducted a systematic review and network meta-analysis of randomized controlled trials that meet the inclusion criteria to explore the intervention effects of five different types of mind-body exercises in improving anxiety and depression in older adults.ii. Methods: We followed the PRISMA-NMA guidelines and conducted searches in the Web of Science, PubMed, the Cochrane Library, and Embase databases up to July 28, 2023. The language was limited to English. Two independent reviewers conducted literature screening and data extraction.Review Manager 5.4 was used to perform Pairwise meta-analysis and risk assessment, while STATA version 15 software was used for network meta-analysis.iii. Result: A total of 42 studies, involving 2974 participants, were included. The results of the traditional meta-analysis showed that mind-body exercises were superior to the control group in alleviating anxiety (SMD: -0.87, 95% CI: -1.43, -0.31, p<0.05, I 2 =95%) and depressive (SMD: -0.52, 95% CI: -0.71, -0.34, p<0.05, I 2 =80%). In the network meta-analysis, the ranking of treatment effects for anxiety showed that Tai Chi > Qigong > Yoga > Dance > control group, while for depression, the ranking showed Tai Chi > Pilates > Yoga > Qigong > Dance > control group. iv. Conclusion: This study found that mind-body exercises have positive effects on improving anxiety and depression in older adults. Among the five different types of mind-body exercise interventions, Tai Chi was considered an effective approach for improving anxiety and depression.However, we encourage older adults to choose exercise modalities that suit their interests to enhance adherence.Anxiety and depression have become one of the most common mental health problems globally, affecting approximately 340 million people(1). Research by Hay et al. indicates that between 2005 and 2015, the prevalence of anxiety increased by 14.9% and the prevalence of depression increased